2012
DOI: 10.1186/1471-2407-12-586
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1 expression patterns in different Hodgkin lymphoma subtypes and progressively transformed germinal centers

Abstract: BackgroundIncreased glycolytic activity is a hallmark of cancer, allowing staging and restaging with 18F-fluorodeoxyglucose-positron-emission-tomography (PET). Since interim-PET is an important prognostic tool in Hodgkin lymphoma (HL), the aim of this study was to investigate the expression of proteins involved in the regulation of glucose metabolism in the different HL subtypes and their impact on clinical outcome.MethodsLymph node biopsies from 54 HL cases and reactive lymphoid tissue were stained for glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…c ). The present results are consistent with our previous findings demonstrating increased expression patterns of the glucose transporter GLUT1 and decreased levels of the lactate transporters MCT1 and MCT4 in a series of primary Hodgkin cases . Moreover, the higher respiratory control ratios we observed (Figs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…c ). The present results are consistent with our previous findings demonstrating increased expression patterns of the glucose transporter GLUT1 and decreased levels of the lactate transporters MCT1 and MCT4 in a series of primary Hodgkin cases . Moreover, the higher respiratory control ratios we observed (Figs.…”
Section: Discussionsupporting
confidence: 93%
“…The present results are consistent with our previous findings demonstrating increased expression patterns of the glucose transporter GLUT1 and decreased levels of the lactate transporters MCT1 and MCT4 in a series of primary Hodgkin cases. 28 Moreover, the higher respiratory control ratios we observed ( Figs. 2b and 2c) indicated that the increase in respiration was not associated with an increased proton leak across the inner mitochondrial membrane.…”
Section: Discussion Chl Cells Adapt In a Non-warburg Mannermentioning
confidence: 58%
“…Burkitt lymphoma, follicular lymphoma, DLBCL and primary effusion lymphoma (PEL) lines show increased glycolytic flux (Bhatt et al, 2012). In many patients, Hodgkin and Reen Stenberg cells express high levels of the glucose transporter Glut1 and glycolytic enzymes such as lactate dehydrogenase (LDHA) (Hartmann et al, 2012). In comparison to B cells from healthy donors, primary B cell acute lymphoblastic leukemia (B-ALL) cells show increased rates of aerobic glycolysis and decreased survival after 2-DG inhibition (Liu et al, 2014).…”
Section: Metabolic Signatures Of B Cell Derived Malignanciesmentioning
confidence: 99%
“…It has been shown that different mechanisms of glucose uptake, e.g. via GLUT1 in HRS cells and via GLUT3 in the microenvironment, contribute to PET positivity of the tumour [8]. In a recent study no correlation was found between GLUT1 expression in HRS cells and PET standard uptake values, and significant differences in progression-free survival (PFS) or OS between patients exhibiting different GLUT1 expression patterns could not be demonstrated.…”
mentioning
confidence: 92%
“…In a recent study no correlation was found between GLUT1 expression in HRS cells and PET standard uptake values, and significant differences in progression-free survival (PFS) or OS between patients exhibiting different GLUT1 expression patterns could not be demonstrated. Indeed the surrounding mononuclear cells account for 99 % of the Hodgkin tumour and it has been shown that HL cell lines cultured in vitro were characterized by a very high metabolic activity [8]. This suggests that these environmental cells are responsible in vivo for the FDG uptake in baseline FDG PET scans.…”
mentioning
confidence: 94%